Do ETFs increase liquidity? - Mehmet Saæglam; Tugkan Tuzun; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2021)
This paper investigates the impact of exchange-traded funds (ETFs) on the liquidity of their underlying stockholdings. Using a difference-in-differences methodology for large changes in the index weights of stocks in the S&P 500 and NASDAQ 100 indexes, we find that increases in ETF ownership are associated with increases in commonly used measures of liquidity. Stocks with high ETF ownership have higher price resilience and lower adverse selection costs. However, ETFs are linked to higher liquidation costs during the 2011 U.S. debt-ceiling crisis, suggesting that stocks with high ETF ownership may experience impaired liquidity during major market stress events.
Keywords: 330